Acute Kidney Injury Defined by Fluid Corrected Creatinine in Neonates After the Norwood Procedure. Issue 5 (September 2018) - SooHoo, Megan McFerson; Patel, Sonali S.; Jaggers, James; Faubel, Sarah; Gist, Katja M.
Background: Both the Norwood procedure and acute kidney injury (AKI) are associated with significant morbidity and mortality. The impact of AKI by measured and fluid corrected serum creatinine on outcomes after the Norwood procedure has not been previously studied. The purpose of this study was to (1) identify the incidence of AKI, (2) determine AKI risk factors, and (3) evaluate outcomes in patients with AKI using both measured and fluid corrected serum creatinine. Methods: Single-center retrospective chart review from 2009 to 2015 including neonates who underwent the Norwood procedure. Acute kidney injury was defined by the Kidney Disease Improving Global Outcomes staging criteria using both measured and fluid corrected serum creatinine. Multivariable logistic regression analysis was performed to determine the risk factors associated with AKI. Results: Ninety-five neonates underwent the Norwood procedure. Correcting for fluid overload increased the incidence of AKI from 40% to 44%, increased AKI severity in 15 patients, and improved the identification of adverse outcomes associated with AKI. Patients palliated with the modified Blalock-Taussig shunt (mBTS) had a 9.4 greater odds of fluid corrected AKI compared to those palliated with a right ventricle to pulmonary artery conduit (95% confidence interval [95% CI]: 1.68-52.26, P = .01). A higher vasoactive inotrope score (VIS) on postoperative day (POD) 0 was associated with fluid corrected AKI (odds ratio: 1.20, 95% CI: 1.06-1.35; P = .003). Conclusions: Acute kidney injury is common after the Norwood procedure. Correcting creatinine for fluid balance revealed new cases of AKI. Use of an mBTS and higher VIS on POD 0 were associated with increased risk of AKI.